College Students' Perceptions of Personal Learning Environments Through the Lens of Digital Tools, Processes and Spaces - Nada Dabbagh; Helen Fake (Springer, 2017)
A review of the literature reveals there is a gap in the research regarding how students currently perceive PLEs and how they structure their PLEs to support their learning goals. The purpose of this study was to establish an understanding of college students' perceptions of PLEs and what digital tools are currently being used to structure PLEs in order to facilitate personal growth and development. Participants (N=109) were asked to share their perceptions of PLEs and what digital tools, devices, and services they use to create PLEs. Analysis of blog submissions revealed similarities and differences between the ways that undergraduate and graduate students perceive PLEs and how they characterize these learning spaces. Students reported using a variety of digital tools for learning however their expectations of digital tools were to foster discussion, collaboration, and interaction, organization, planning, and resource management, experiential learning, personalization and a desire for effective technology. The findings of this study have important implications with respect to the competencies and skills needed to create effective PLEs and the affordances of digital technologies needed to support PLE development.